World economy: What does the road to recovery from COVID-19 look like? Expert survey on worldwide effects of the pandemic - Dorine Boumans; Pauliina Sandqvist; Stefan Sauer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
As the economy and our daily life return to a "new-normal" in the midst of Covid-19, the possibility of a second wave leaves lots of uncertainty about future developments. To understand indications about the impact of the pandemic on economic performance in different countries across the world, we conducted a survey among 950 economic experts in 110 countries. This report gives an overview of the most important results of the survey and compares them in different world regions and countries. An extra focus is placed on the European Union's strategy to combat the crisis and how experts from member states assess the different policy measures.
Keywords: 330; Internationale Wirtschaft; Coronavirus; Wirkungsanalyse; Erhebungstechnik; Welt